The Gibson paradox: real gold, interest rates and prices - Abdullah, Adam (Canadian Center of Science and Education, 2013)
This paper aims to provide an analysis and explanation of the curious empirical relationships that exist between the price of gold, the interest rate and commodity prices, operating under the English 19th century fractional reserve gold standard and the modern American fractional reserve fiat paper standard, known as the Gibson Paradox. This paper argues that the value and purchasing power of the British pound and American dollar are managed in relation to their rate of exchange with gold and the real rate of interest, such that, changes in the general level of prices are the effect and not the cause.